(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
Clinical Behavior Analysis (CBA) holds similar assumptions to those APA posits for Evidence-based Practice (EBP). However, such familiarity does not ensure the adequacy of Brazilian production to APA’s guidelines. The aim of this study is to verify possible relations between Brazilian CBA production and guidelines stablished by APA, by means of a literature review. According to PRISMA protocol, among the 353 eligible publications, 172 were included. Conceptual results (107) were introduced to IRaMuTeQ, demonstrating a growing use of terms regarding PBE after 2017. Empiric studies (65) had their methodology analysed, observing compatibilities with PBE’s recommendations. But, a single study proposed functional analysis and none of them reported the assessment of client satisfaction. Results suggest that APA’s guidelines may have influenced on national produçtion, but further studies should refine the analyses to boost valid inferences about such relations.